Failure Of Diversion And Fulfillment Of The Best Interests Of Children In Conflict With The Law - Waluyadi; Muslikhah; Mariana, Montisa (Universitas Negeri Semarang, 2024)
This study critically examines the failure of diversion programs in fulfilling the best interests of children in conflict with the law. Diversion, which aims to redirect juvenile offenders from the formal justice system toward rehabilitation, has been a key principle in juvenile justice systems. However, its failure to achieve effective outcomes—particularly in safeguarding children’s rights and welfare—remains a pressing concern. This research aims to identify the factors contributing to the failure of diversion, associating these with the broader endeavor to protect and promote the best interests of children. The study reveals several factors leading to the failure of diversion: the lack of consensus between victims and offenders or their families, the non-implementation of agreements, and differing interpretations of key legal provisions under Article 3 of Perma No. 4 of 2014 and Article 7 of the Juvenile Criminal Justice System Law (SPPA). These factors have contributed to inconsistencies in the application of diversion measures. Despite these failures, the study finds that the law still offers avenues for protecting the best interests of children, particularly when diversion is successful. Achieving effective diversion can lead to faster, simpler, and lower-case examinations, promoting rehabilitation and reintegration over punishment. The study contributes to the national and global discourse on juvenile justice by highlighting the challenges of implementing diversion programs and offering insights for reform.